Essays on trust in the judicial system: evidence from Brazil - Sampaio, Joelson Oliveira (2015)
A factor that crucially affects the development of a country is the ability of its judiciary to present itself as a legitimate instance for resolving the disputes that arise in social and economic affairs. One way to approach this topic is to study the reasons that lead citizens to trust or to distrust the judiciary. Thus, this thesis analyzes the determinants of public trust in the judicial system in Brazil; it also attempts to determine the drivers that lead people to trust or to distrust it. Chapter 2 addresses the relationship between trust in the judicial system and economic and demographic variables such as race, income, age, gender, education, previous experience with the judicial system, and knowledge about the legal system. The Brazilian Confidence in Justice Index (BCJI) was built as a trust measure. The BCJI is a measure of perception which reveals the opinion of the population regarding Brazil\'s judiciary system. The results indicate that race and gender are important predictors, once controlled for other respondent characteristics. Black persons have a slightly lower level of trust in the judiciary than do non-black persons. Women also espress less trust than men. Finally, the results indicate that poorer people also have lower levels of trust in the judicial system. Although there is a substantial literature that relates the determinants of trust in the judicial system and use of the judiciary, the causal relationship between these two variables is unclear. The purpose of Chapter 3 is to examine this causal relationship in Brazil. The results indicate that trust in the judicial system has a positive impact on use of the judiciary. That is, individuals who have higher levels of trust in the judicial system have a greater propensity to seek the judiciary. There is also a statically significant relationship between trust in the judicial system and use of the judiciary for some economic and demographic variables, such as income, education, age, and race. There is a widespread belief that the police is the government\'s first-line representative, responsible for controlling the social order. Policy-makers and members of the public have long been concerned about the number of police officers who are effectively deployed to reduce crime. Chapter 4 analyzes the relationship between crime rates and trust in the police. For example, do regions with higher crime rates display lower trust in the police? It is in this sense that this Chapter studies the motivations that lead citizens to trust or to distrust the police. The results indicate that in general there is a negative relationship between an increase on the crime rate and trust in the police. Such results are even stronger for some less common crimes such as drug dealing and rape. The results also indicate that those who have had previous experience with the police do not seem to associate police work with crime rates, in contrast with those who have never had a previous experience. Finally, Chapter 5 summarizes all of the findings from the previous Chapters and discusses possible future directions of research.